Cryptococcosis in pregnancy and the postpartum period: Case series and systematic review with recommendations for management. (13th August 2019) - Pastick, Katelyn A; Nalintya, Elizabeth; Tugume, Lillian; Ssebambulidde, Kenneth; Stephens, Nicole; Evans, Emily E; Ndyetukira, Jane Frances; Nuwagira, Edwin; Skipper, Caleb; Muzoora, Conrad; Meya, David B; Rhein, Joshua; et al.
Abstract: Cryptococcal meningitis causes 15% of AIDS-related deaths. Optimal management and clinical outcomes of pregnant women with cryptococcosis are limited to case reports, as pregnant women are often excluded from research. Amongst pregnant women with asymptomatic cryptococcosis, no treatment guidelines exist. We prospectively identified HIV-infected women who were pregnant or recently pregnant with cryptococcosis, screened during a series of meningitis research studies in Uganda from 2012 to 2018. Among 571 women screened for cryptococcosis, 13 were pregnant, one was breastfeeding, three were within 14 days postpartum, and two had recently miscarried. Of these 19 women (3.3%), 12 had cryptococcal meningitis, six had cryptococcal antigenemia, and one had a history of cryptococcal meningitis and was receiving secondary prophylaxis. All women with meningitis received amphotericin B deoxycholate (0.7–1.0 mg/kg). Five were exposed to 200–800 mg fluconazole during pregnancy. Of these five, three delivered healthy babies with no gross physical abnormalities at birth, one succumbed to meningitis, and one outcome was unknown. Maternal meningitis survival rate at hospital discharge was 75% (9/12), and neonatal/fetal survival rate was 44% (4/9) for those mothers who survived. Miscarriages and stillbirths were common ( n = 4). Of six women with cryptococcal antigenemia, two received fluconazole, one received weekly amphotericin B, and three had unknown treatment courses. All women with antigenemia survived, and none developed clinical meningitis. We report good maternal outcomes but poor fetal outcomes for cryptococcal meningitis using amphotericin B, without fluconazole in the first trimester, and weekly amphotericin B in place of fluconazole for cryptococcal antigenemia.